Hope across cultural groups. (February 2023) - Edwards, Lisa M.; McConnell, Kat
Abstract: Over the past 30 years, there has been an increasing amount of research about hope and culture. While early studies focused on looking at differences in hope between racial groups, recent research has focused more broadly on the measurement of hope and how hope operates in diverse contexts and nations. Many translations of the adult and child versions of the hope scale now exist, though questions about the structure of hope (e.g., pathways and agency) have been raised in certain groups. Paradoxically, recent research suggests that higher levels of hope are associated with less well-being for those experiencing racial discrimination. Finally, hope has started to be explored in other aspects of identity including disability, religion/spirituality, and sexual orientation, emphasizing the importance of context when understanding hope. Highlights: Hope is influenced by cultural context. There are many translations of adult and child versions of the hope scale. Hope may operate differently in different cultural groups. Hope is related to positive constructs in many groups. In certain stressful contexts hope has been found to be related to lower well-being.